COmmunication’s ROugh NAvigations: ‘Fake’ news in a time of a global crisis (Journal of Applied Learning and Teaching, 2020)
“Disinformation can cost lives” (Ursula von der Leyen, 2020).The current pandemic of the novel coronavirus or COVID-19 has created an environment of diverse challenges facing humanity, including ‘Stay at Home’ global strategies, isolation, social distancing, school and border closures, and widespread travel bans. The risk of this biological threat, its multiple unknown health aspects, social and economic impacts, and the inability of humanity to control it at present makes it difficult to predict how this situation will evolve. Unfortunately, such a global crisis gives rise to the manipulation of people by opportunistic groups through the falsification of information and news reporting. Loosely moderated social media platforms have largely contributed to an explosion of news referred to as ‘fake’.Global occurrences like the current COVID-19 pandemic reinforce the importance of developing critical thinking skills in undergraduate students as a fact-finding strategy to address the rising popularity of misinformation and disinformation found on social media sites. Consequently, this paper aims to highlight the importance of building a capacity to recognise fake news while seeking out reliable and valid information sources. Strategies to address fake news by international and local organisations will be explored using examples from Greece and Australia, as both of these countries demonstrated strong government leadership in the swift containment of the virus. Greece was quick to impose lockdowns that were respected and dutifully exercised by the Greek people. Similarly, Australia also imposed strict lockdowns strategies in the initial stages of their first reported COVID-19 cases and were also dutifully enacted by Australian citizens. Greece and Australia have been proactive in addressing disinformation and misinformation through comprehensive data analytics and fact-checking strategies, which are reported on through official platforms.Specifically, the authors aim to:• Discuss the severe and even fatal problems that misinformation can cause, especially in the case of a global pandemic, like COVID-19,• provide an audit and access to reliable sites,• provide an outline of simple strategies that all individuals (including undergraduate students) can implement to source valid and reliable information surrounding the COVID-19 pandemic.